Bioavailability of once‐daily tacrolimus formulations used in clinical practice in the management of De Novo kidney transplant recipients: the better study. Issue 3 (17th December 2021) - Fernandez Rivera, Constantino; Calvo Rodríguez, María; Poveda, José Luís; Pascual, Julio; Crespo, Marta; Gomez, Gonzalo; Cabello Pelegrin, Sheila; Paul, Javier; Lauzurica, Ricardo; Perez Mir, Mònica; Moreso, Francesc; Perelló, Manel; et al.
Abstract: Multicenter, prospective, observational study to compare the relative bioavailability of once‐daily tacrolimus formulations in de novo kidney transplant recipients. De novo kidney transplant recipients who started a tacrolimus‐based regimen were included 14 days post‐transplant and followed up for 6 months. Data from 218 participants were evaluated: 129 in the LCPT group (Envarsus) and 89 in the PR‐Tac (Advagraf) group. Patients in the LCPT group exhibited higher relative bioavailability (Cmin /total daily dose [TDD]) vs. PR‐Tac (61% increase; P  < .001) with similar Cmin and 30% lower TDD levels ( P  < .0001). The incidence of treatment failure was 3.9% in the LCPT group and 9.0% in the PR‐Tac group ( P = .117). Study discontinuation rates were 6.2% in the LCPT group and 12.4% in the PR‐Tac group ( P = .113). Adverse events, renal function and other complications were comparable between groups. The median accumulated dose of tacrolimus in the LCPT group from day 14 to month 6 was 889 mg. Compared to PR‐Tac, LCPT showed higher relative bioavailability, similar effectiveness at preventing allograft rejection, comparable effect on renal function, safety, adherence, treatment failure and premature discontinuation rates.